2013
DOI: 10.1097/opx.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Presbyopia and Spectacle Coverage in an African Population in Durban, South Africa

Abstract: This study indicated that there is a high prevalence of presbyopia in the study area, with low spectacle coverage, and therefore suggests that uncorrected presbyopia is a major public health concern. The findings of this study may help in making recommendations for strategic planning for eye health intervention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
0
19
1
2
Order By: Relevance
“…The value obtained was multiplied by 1.5 to account for design effect. In accordance with a previous related study conducted in South Africa, 15 the lower age boundary of 35 years for presbyopia was used in the current study. Cape Coast is the capital of the Central region of Ghana.…”
Section: Methodsmentioning
confidence: 99%
“…The value obtained was multiplied by 1.5 to account for design effect. In accordance with a previous related study conducted in South Africa, 15 the lower age boundary of 35 years for presbyopia was used in the current study. Cape Coast is the capital of the Central region of Ghana.…”
Section: Methodsmentioning
confidence: 99%
“…Similar variation is also seen in SC for presbyopia. A study from China reported SC of over 51%, while some studies from Africa and Tanzania reported less than 10% …”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported on the economic impact of uncorrected presbyopia . NVI has been widely studied in the past years . A recent multi‐country study has shown high and a varied prevalence of NVI across different geographical locations suggesting a need for local surveys .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study used a standardised protocol that was developed by an international collaboration led by the National Eye Institute (NEI) in the USA and the World Health Organization (WHO) . The methods have been used previously and reported in several countries, such as China, India, Nepal, Niger, South Africa and the USA . The research area selected was the department of Masaya, which is in the Pacific region of Nicaragua, with a population of approximately 250,000 people, 55.4 per cent of which is urban.…”
Section: Methodsmentioning
confidence: 99%